Green heat-treatment-free die-casting aluminum alloy and preparation method thereof

By adding trace elements such as yttrium, scandium and europium to the die-cast aluminum alloy, refining the Fe-rich phase and controlling the growth of the second phase, the problem of low strength and elongation of the existing aluminum alloy is solved, and high-performance aluminum alloy without heat treatment is achieved, reducing production costs and environmental pollution.

CN119571146APending Publication Date: 2025-03-07YUNNAN ALUMINUM
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411761026.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

Existing die-cast aluminum alloy products have low strength and elongation, and require heat treatment to improve performance. However, the heat treatment process is prone to quality defects such as deformation and bubbles, increasing production costs and environmental pollution.

Method used

By adding yttrium and scandium, the growth of the thick needle-shaped Fe-rich phase is suppressed, and it is refined into a fine and uniform granular form. Combined with other trace elements such as europium, a nano-scale dispersed distribution precipitation phase is formed, and the growth of the second phase Mg2Si is controlled, the grain boundary characteristics are improved, and high toughness and high strength aluminum alloys are achieved.

Benefits of technology

Aluminum alloys that can obtain excellent mechanical properties, thermal conductivity and corrosion resistance without heat treatment are achieved, reducing production costs and environmental pollution, and improving the application prospects of aluminum alloys.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119571146A_ABST
    Figure CN119571146A_ABST
Patent Text Reader

Abstract

The invention provides a green heat-treatment-free die-casting aluminum alloy and a preparation method thereof, and relates to the technical field of aluminum alloys. The aluminum alloy comprises the following components in percentage by mass: 4%-5% of silicon, 0.2%-0.5% of iron, 0.1%-0.5% of copper, 0.1%-0.5% of zinc, 0.3%-0.6% of manganese, 0.1%-0.3% of magnesium, 0.1%-0.5% of cadmium, 0.02%-0.3% of titanium, 0.002%-0.1% of strontium, 0.001%-0.02% of yttrium, 0.002%-0.01% of scandium, 0.001%-0.01% of europium and the balance of aluminum. The composite material has excellent mechanical property, heat-conducting property and corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of aluminum alloys, and in particular to a green aluminum heat-treatment-free die-casting aluminum alloy and a preparation method thereof. Background Art

[0002] With the increasing attention paid to environmental protection and sustainable development around the world, green manufacturing has become an important direction for the development of the aluminum alloy industry. Especially in Yunnan Province, relying on its abundant green aluminum resources, the development of high-performance, environmentally friendly aluminum alloy materials has important economic and social significance.

[0003] At present, the main domestic die-cast aluminum ingot products are traditional ADC12, ADC10, A380, etc., and these die-cast aluminum alloys generally have low strength and elongation, and the two cannot be taken into account at the same time. In addition, the silicon content in existing die-cast aluminum alloy products is relatively high, and it is easy to form coarse needle-shaped eutectic Si and coarse needle-shaped β-AlFeSi phase in the aluminum alloy, which will greatly reduce the elongation of the aluminum alloy and affect the use of the aluminum alloy. In addition, traditional die-cast aluminum alloys usually need to undergo heat treatment to improve their performance, and there are many uncontrollable factors in the heat treatment process, which will eventually lead to quality defects such as deformation and blistering of die-cast parts after heat treatment. This process not only increases production costs, energy consumption and environmental pollution, but also affects the quality of aluminum alloys. Summary of the invention

[0004] The object of the present invention is to provide a green aluminum heat-treatment-free die-casting aluminum alloy, which has excellent mechanical properties, thermal conductivity and corrosion resistance.

[0005] Another object of the present invention is to provide a method for preparing a green aluminum heat-treatment-free die-cast aluminum alloy, which achieves the goal of high performance and lightweight of the die-cast aluminum alloy and has broad application prospects.

[0006] The embodiments of the present invention are implemented by the following technical solutions:

[0007] A green aluminum heat-treatment-free die-casting aluminum alloy comprises the following components by mass fraction: 4-5% silicon, 0.2-0.5% iron, 0.1-0.5% copper, 0.1-0.5% zinc, 0.3-0.6% manganese, 0.1-0.3% magnesium, 0.1-0.5% cadmium, 0.02-0.3% titanium, 0.002-0.1% strontium, 0.001-0.02% yttrium, 0.002-0.01% scandium, 0.001-0.01% europium, and the balance is aluminum.

[0008] A method for preparing a green aluminum heat-treatment-free die-casting aluminum alloy comprises the following steps:

[0009] Melting aluminum ingots, silicon, iron, copper, zinc, manganese, magnesium, cadmium, titanium, and green aluminum raw materials to prepare a first aluminum alloy melt;

[0010] Adding strontium, yttrium, scandium and europium raw materials into the first aluminum alloy melt for smelting to obtain a second aluminum alloy melt;

[0011] Adding a degassing agent to the second aluminum alloy melt for refining treatment, and slagging to obtain a third aluminum alloy melt;

[0012] The third aluminum alloy melt is die-casted to obtain a lightweight heat-treatment-free die-cast aluminum alloy.

[0013] The technical solution of the embodiment of the present invention has at least the following advantages and beneficial effects:

[0014] In the present invention, by adding yttrium and scandium, both yttrium and scandium have an inhibitory effect on the growth of coarse needle-shaped Fe-rich phase, but cannot completely eliminate the coarse needle-shaped Fe-rich phase. The Fe-rich phase is refined and modified by the interaction of the two, and the growth of the Fe-rich phase in the needle direction can be completely inhibited, so that the Fe-rich phase is changed from coarse needle-shaped to fine and uniform granular, and the influence of rich Fe on the strength and plasticity of the aluminum alloy is eliminated. Yttrium and scandium can also form a nano-scale dispersed precipitation phase, which can refine α-Al and eutectic silicon grains while controlling the growth of the second phase Mg2Si, thereby obtaining a fine and uniformly distributed second phase, and can also reduce the enrichment of the low-melting point coarse second phase at the grain boundary, thereby improving the thermal fission tendency, corrosion resistance and mechanical properties of the aluminum alloy. Europium (Eu) can not only adsorb on the <112> direction of eutectic silicon, poisoning the unique twin groove growth mechanism of eutectic silicon, but also rare earth Eu atoms can adsorb on the {111} plane of eutectic silicon, promoting the formation of twins and thus changing the growth direction of eutectic silicon. Yttrium, scandium and europium are mainly enriched at the grain boundary position, eliminating the harmful effects of impurity elements, and interacting with other alloy elements to form compounds and change the alloy structure.

[0015] By combining silicon, iron, copper, manganese, zinc, magnesium, cadmium and other trace elements in specific proportions, and utilizing mechanisms such as solid solution strengthening, second phase strengthening, grain refinement, and improved grain boundary properties, high toughness and high strength can be achieved in the cast state. This allows aluminum alloys with excellent mechanical properties, thermal conductivity and corrosion resistance to be obtained without subsequent heat treatment, achieving the goals of high performance and lightweight, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is a metallographic image of a longitudinal section of an aluminum alloy sample according to Example 1 of the present invention;

[0017] Figure 2 This is a longitudinal cross-sectional scan of the aluminum alloy sample of Example 1 of the present invention;

[0018] Figure 3This is a metallographic image of a longitudinal section of an aluminum alloy sample according to Example 2 of the present invention;

[0019] Figure 4 This is a longitudinal cross-sectional scan of an aluminum alloy sample according to Example 2 of the present invention;

[0020] Figure 5 This is a metallographic image of a longitudinal section of an aluminum alloy sample according to Example 3 of the present invention;

[0021] Figure 6 This is a longitudinal cross-sectional scan of an aluminum alloy sample according to Example 3 of the present invention;

[0022] Figure 7 This is a metallographic image of a longitudinal section of an aluminum alloy sample according to Example 4 of the present invention;

[0023] Figure 8 This is a scanning diagram of the longitudinal section of the aluminum alloy sample of Example 4 of the present invention. DETAILED DESCRIPTION

[0024] The present invention is further described below in conjunction with specific embodiments, but the embodiments do not limit the present invention in any form. Unless otherwise specified, the raw materials and reagents used in the embodiments of the present invention are conventionally purchased raw materials and reagents.

[0025] A green aluminum heat-treatment-free die-casting aluminum alloy comprises the following components by mass fraction: 4-5% silicon, 0.2-0.5% iron, 0.1-0.5% copper, 0.1-0.5% zinc, 0.3-0.6% manganese, 0.1-0.3% magnesium, 0.1-0.5% cadmium, 0.02-0.3% titanium, 0.002-0.1% strontium, 0.001-0.02% yttrium, 0.002-0.01% scandium, 0.001-0.01% europium, and the balance is aluminum.

[0026] Silicon (Si): Silicon forms fine β-Al FeSi phase in aluminum alloy, which helps to improve the plastic processing performance and high temperature strength of the alloy. The increase of silicon content can enhance the wear resistance and hardness of the alloy. By controlling the silicon content in the components and adding Mn and Eu to change the morphology of the β-Al FeSi phase, the morphology of the β-Al FeSi phase is changed to a fine β-Al FeSi phase or α-Al FeSi phase. By controlling the β-Al FeSi phase, the stress concentration effect of the needle phase is reduced and the elongation of the alloy is increased. At the same time, this content can inhibit the growth of coarse needle-like eutectic Si, turning it into a fine fibrous structure and refining the eutectic silicon particle size.

[0027] Iron (Fe): Iron mainly forms α-Al FeSi phase in aluminum alloy, which can improve the strength and hardness of the alloy. At the same time, the addition of iron is conducive to the demoulding of thin-walled parts, reduces deformation caused by demoulding problems, and improves the yield rate. However, when the iron content is too high, it will be distributed in the aluminum alloy matrix in the form of coarse needle-shaped Fe-rich phase. The coarse needle-shaped Fe-rich phase will seriously split the aluminum alloy matrix, resulting in low strength and toughness of the aluminum alloy. Therefore, the iron content needs to be controlled at 0.2-0.5%.

[0028] Manganese (Mn): Manganese can change the morphology of the iron phase. The addition of Mn can promote the transformation of β-Al FeSi into α-Al FeSi. Manganese forms MnAl6 compound dispersed particles in aluminum alloys, which hinders the growth of recrystallized grains and refines recrystallized grains; at the same time, it can dissolve iron to form (Fe, Mn)Al6, reducing the adverse effects of iron. Manganese can also improve the corrosion resistance and processing properties of the alloy, but excessive manganese may lead to the formation of large blocks of α-Al FeSi, which is not conducive to the mechanical properties of the alloy. Therefore, the manganese content should be controlled at 0.3%-0.6%.

[0029] Copper (Cu): The addition of copper can form CuAl2 phase, which changes the phase structure of the alloy's precipitation phase and forms a fine second phase, which plays a role in strengthening dispersion and improving the strength and heat resistance of the alloy. Copper can also enhance the electrical conductivity of the alloy, but too high a content may reduce the plasticity of the alloy.

[0030] Magnesium (Mg): Magnesium usually forms Mg2Si phase in aluminum alloy, which improves the high temperature strength and rigidity of the alloy. Magnesium can also improve the corrosion resistance of the alloy. However, if the magnesium content is too high, the Mg2Si phase and intermetallic compounds formed will cause lattice distortion, increase the inhomogeneity of the structure, cause the scattering of electron waves, and reduce the thermal conductivity and mechanical properties of the alloy. Therefore, the magnesium content is controlled at 0.1%-0.3%.

[0031] Zinc (Zn): The addition of zinc can form η-Al ZnMg phase, improving the strength and heat resistance of the alloy. Zinc can also improve the creep resistance of the alloy, but excessive zinc may cause the alloy to become brittle.

[0032] In aluminum alloys, although magnesium and zinc have high solid solubility in Al, when magnesium and zinc are added alone, it is impossible to achieve a high strength level due to the weak aging hardening effect. When zinc and magnesium coexist, a series of precipitation hardening phases are formed due to the high solubility of η-Al ZnMg phase in Al and the obvious temperature relationship, which produces a strong aging hardening effect and improves the strength of the alloy. The strength of the alloy increases with the increase of the total amount of zinc and magnesium, but when it exceeds a certain amount, the alloy is in a brittle state due to the precipitation of a continuous network of brittle phases at the grain boundaries, resulting in alloy fracture, reduced toughness and stress resistance, corrosion resistance, and weakened organizational stability. Therefore, 0.1-0.5% zinc and 0.1-0.3% magnesium are selected.

[0033] Titanium (Ti): Titanium mainly forms Al3Ti phase in aluminum alloy, providing heterogeneous nucleation points for the alloy and promoting the nucleation of eutectic Si phase, thereby achieving the purpose of refining the eutectic Si phase and α-Al phase; it can also purify the melt and improve the toughness and corrosion resistance of the alloy.

[0034] Cadmium (Cd): Cadmium can dissolve in aluminum alloys to form a solid solution of aluminum alloys. The formation of solid solution can improve the hardness, strength and wear resistance of aluminum alloys. In addition, cadmium can also improve the grain boundary characteristics of the alloy, hinder dislocation movement and crack propagation, and improve the toughness of aluminum alloys.

[0035] Strontium (Sr): As a trace element, strontium can transform the original coarse needle-like eutectic Si into a fine fibrous structure through modification, refine the eutectic silicon particle size, weaken the splitting effect of eutectic silicon on the matrix, change the microstructure of the alloy, and improve the plasticity of the alloy. The addition of strontium helps to reduce inclusions in the alloy and improve the processing performance of the alloy.

[0036] A method for preparing a green aluminum heat-treatment-free die-casting aluminum alloy comprises the following steps:

[0037] Melting aluminum ingots, silicon, iron, copper, zinc, manganese, magnesium, cadmium, titanium, and green aluminum raw materials to prepare a first aluminum alloy melt;

[0038] Adding strontium, yttrium, scandium and europium raw materials into the first aluminum alloy melt for smelting to obtain a second aluminum alloy melt;

[0039] Adding a degassing agent to the second aluminum alloy melt for refining treatment, and slagging to obtain a third aluminum alloy melt;

[0040] The third aluminum alloy melt is die-casted to obtain a lightweight heat-treatment-free die-cast aluminum alloy.

[0041] Green aluminum can be electrolytic aluminum produced through the ASI green system or green recycled aluminum.

[0042] Furthermore, the degassing agent includes, by weight, 20-30 parts of magnesium chloride, 20-30 parts of potassium chloride, 10-20 parts of potassium fluoroaluminate, 20-30 parts of aluminum fluoride and 10-20 parts of graphite / nano-molybdenum nitride composite.

[0043] Chlorides and fluorides in the flux remove hydrogen and other gases from the aluminum liquid through physical and chemical reactions, adsorb and remove oxide inclusions. The two chlorides act as basic items to reduce the melting point. Fluorides usually have a high affinity for oxygen and can react with oxygen in the aluminum liquid to form insoluble oxides, thereby reducing pores and other defects. These components play a role in removing gases and impurities from the aluminum melt during the refining process. Potassium fluoroaluminate (KAl F4) and aluminum fluoride (Al F3) may form complexes or react with hydrogen to form insoluble fluorides, thereby achieving degassing. In addition, these fluorides can then be separated from the aluminum liquid in the form of precipitation, forming scum on the surface of the aluminum liquid and removed.

[0044] The melting point of magnesium chloride and potassium chloride complex is low, about 250-450℃. It melts into droplets in high-temperature aluminum liquid, and the droplet density is about 1.1-16g / cm 3 , and has good wettability, can infiltrate oxides, and take oxides away from the aluminum liquid. At the same time, after reaching the surface of the aluminum liquid, the slag is mixed with the flux complex, and the complex is in a lamellar form, which can break up the slag and facilitate the aluminum liquid to flow back into the aluminum liquid in drops, achieving the aluminum slag separation effect. Magnesium chloride and potassium chloride: form complexes at high temperatures, which help to adsorb and remove hydrogen and other gases in the aluminum melt.

[0045] Since graphite is easy to aggregate and precipitate during the refining process, the graphite's adsorption performance for impurities during the refining process is affected. Therefore, nano-molybdenum nitride is used to composite graphite. The nano-molybdenum nitride has a small particle size and is evenly distributed on the surface and between the graphite sheets. While increasing the specific surface area and porosity of graphite, it can improve the bonding ability between graphites, improve the adsorption and dispersion uniformity of graphite in the melt, and enhance its adsorption capacity for impurities. In addition, during the refining process, the nitrogen generated by the reaction of nano-molybdenum nitride and oxidized impurities can adsorb impurities in aluminum oxide and take away hydrogen in the melt. Molybdenum can form a fine second phase precipitation in the aluminum alloy, which plays a role in strengthening dispersion and improving the strength of the alloy.

[0046] The preparation method of the graphite / nano-molybdenum nitride composite is as follows: graphite is made into expanded graphite, a nano-molybdenum source is dissolved in a solvent to prepare a dispersion, the dispersion is injected between the expanded graphite layers under vacuum pressure, the solvent is evaporated, heated and oxidized, and then nitrided in a nitrogen atmosphere to obtain the composite.

[0047] During the refining process, chlorine is also introduced into the refining system at a flow rate of 20-30L / min. Chlorine can further remove hydrogen and other gases in the aluminum melt and improve the smelting quality. Chlorine reacts with hydrogen in the aluminum melt to produce hydrogen chloride (HCl), which is a volatile gas that can be removed by a vacuum system to purify the aluminum melt.

[0048] The refining time is 10-20 minutes, and the mixture is allowed to stand for 5-10 minutes after refining.

[0049] During die casting, the pressure is 60-70MPa, the temperature of the third aluminum alloy melt is 680-690℃, the mold temperature is 160-170℃, the speed is 3-4.5m / s, and the vacuum degree is 10-50mbar. You can use 500T LJ die casting machine, automatic ladle feeder, mold temperature controller, brand vacuum machine and other equipment, as well as imported release agent for die casting structural parts on the market, imported granular beads and other auxiliary accessories.

[0050] Example 1

[0051] A green aluminum heat-treatment-free die-casting aluminum alloy comprises the following components by mass fraction: 4.5% silicon, 0.3% iron, 0.2% copper, 0.3% zinc, 0.5% manganese, 0.2% magnesium, 0.3% cadmium, 0.1% titanium, 0.05% strontium, 0.01% yttrium, 0.005% scandium, 0.002% europium, and the balance is aluminum.

[0052] A method for preparing a green aluminum heat-treatment-free die-casting aluminum alloy comprises the following steps:

[0053] Melting aluminum ingots, silicon, iron, copper, zinc, manganese, magnesium, cadmium, titanium, and green aluminum raw materials according to the above ratio to prepare a first aluminum alloy melt;

[0054] Adding strontium, yttrium, scandium and europium raw materials into the first aluminum alloy melt for smelting to obtain a second aluminum alloy melt;

[0055] Adding a degassing agent to the second aluminum alloy melt for refining treatment, the refining time is 10 minutes, and also including introducing chlorine gas into the refining system at a flow rate of 20L / min, standing for 5 minutes after refining to remove slag, to obtain a third aluminum alloy melt;

[0056] The third aluminum alloy melt is die-casted at a pressure of 60 MPa, a temperature of 680° C., a mold temperature of 160° C., a speed of 3 m / s, and a vacuum degree of 10 mbar to obtain a lightweight heat-treatment-free die-cast aluminum alloy.

[0057] The degassing agent includes 20 kg of magnesium chloride, 20 kg of potassium chloride, 10 kg of potassium fluoroaluminate, 20 kg of aluminum fluoride and 10 kg of graphite / nano-molybdenum nitride composite.

[0058] Example 2

[0059] A green aluminum heat-treatment-free die-casting aluminum alloy comprises the following components by mass fraction: 4% silicon, 0.4% iron, 0.4% copper, 0.1% zinc, 0.3% manganese, 0.15% magnesium, 0.5% cadmium, 0.25% titanium, 0.1% strontium, 0.001% yttrium, 0.01% scandium, 0.01% europium, and the balance is aluminum.

[0060] A method for preparing a green aluminum heat-treatment-free die-casting aluminum alloy comprises the following steps:

[0061] Melting aluminum ingots, silicon, iron, copper, zinc, manganese, magnesium, cadmium, titanium, and green aluminum raw materials according to the above ratio to prepare a first aluminum alloy melt;

[0062] Adding strontium, yttrium, scandium and europium raw materials into the first aluminum alloy melt for smelting to obtain a second aluminum alloy melt;

[0063] Adding a degassing agent to the second aluminum alloy melt for refining treatment, the refining time is 20 minutes, and also including introducing chlorine gas into the refining system at a flow rate of 30L / min, standing for 10 minutes after refining to remove slag, to obtain a third aluminum alloy melt;

[0064] The third aluminum alloy melt is die-casted at a pressure of 70 MPa, a temperature of 690° C., a mold temperature of 170° C., a speed of 4.5 m / s, and a vacuum degree of 50 mbar to obtain a lightweight die-cast aluminum alloy that does not require heat treatment.

[0065] The degassing agent includes 30 kg of magnesium chloride, 30 kg of potassium chloride, 20 kg of potassium fluoroaluminate, 30 kg of aluminum fluoride and 20 kg of graphite / nano-molybdenum nitride composite.

[0066] Example 3

[0067] A green aluminum heat-treatment-free die-casting aluminum alloy comprises the following components by mass fraction: 4.4% silicon, 0.2% iron, 0.5% copper, 0.4% zinc, 0.4% manganese, 0.1% magnesium, 0.4% cadmium, 0.3% titanium, 0.004% strontium, 0.005% yttrium, 0.006% scandium, 0.008% europium, and the balance is aluminum.

[0068] A method for preparing a green aluminum heat-treatment-free die-casting aluminum alloy comprises the following steps:

[0069] Melting aluminum ingots, silicon, iron, copper, zinc, manganese, magnesium, cadmium, titanium, and green aluminum raw materials according to the above ratio to prepare a first aluminum alloy melt;

[0070] Adding strontium, yttrium, scandium and europium raw materials into the first aluminum alloy melt for smelting to obtain a second aluminum alloy melt;

[0071] Adding a degassing agent to the second aluminum alloy melt for refining treatment, the refining time is 12 minutes, and also includes introducing chlorine gas into the refining system at a flow rate of 22L / min, standing for 8 minutes after refining to remove slag, to obtain a third aluminum alloy melt;

[0072] The third aluminum alloy melt is die-casted at a pressure of 65 MPa, a temperature of 688° C., a mold temperature of 165° C., a speed of 4 m / s, and a vacuum degree of 30 mbar to obtain a lightweight die-cast aluminum alloy that does not require heat treatment.

[0073] The degassing agent includes 21 kg of magnesium chloride, 22 kg of potassium chloride, 15 kg of potassium fluoroaluminate, 25 kg of aluminum fluoride and 15 kg of graphite / nano-molybdenum nitride composite.

[0074] Example 4

[0075] A green aluminum heat-treatment-free die-casting aluminum alloy comprises the following components by mass fraction: 5% silicon, 0.5% iron, 0.1% copper, 0.5% zinc, 0.3-0.6% manganese, 0.3% magnesium, 0.1% cadmium, 0.02% titanium, 0.002% strontium, 0.02% yttrium, 0.002% scandium, 0.001% europium, and the balance is aluminum.

[0076] A method for preparing a green aluminum heat-treatment-free die-casting aluminum alloy comprises the following steps:

[0077] Melting aluminum ingots, silicon, iron, copper, zinc, manganese, magnesium, cadmium, titanium, and green aluminum raw materials according to the above ratio to prepare a first aluminum alloy melt;

[0078] Adding strontium, yttrium, scandium and europium raw materials into the first aluminum alloy melt for smelting to obtain a second aluminum alloy melt;

[0079] Adding a degassing agent to the second aluminum alloy melt for refining treatment, the refining time is 18 minutes, standing for 8 minutes after refining, and slagging to obtain a third aluminum alloy melt;

[0080] The third aluminum alloy melt is die-casted at a pressure of 67 MPa, a temperature of 684°C, a mold temperature of 163°C, a speed of 3.5 m / s, and a vacuum degree of 40 mbar to obtain a lightweight die-cast aluminum alloy that does not require heat treatment.

[0081] The degassing agent includes 26 kg of magnesium chloride, 22 kg of potassium chloride, 16 kg of potassium fluoroaluminate, 24 kg of aluminum fluoride and 18 kg of graphite / nano-molybdenum nitride composite.

[0082] Comparative Example 1

[0083] The difference between this comparative example and Example 1 is that the silicon content is 6%. The rest is the same as Example 1.

[0084] Comparative Example 2

[0085] The difference between this comparative example and Example 1 is that the content of yttrium is 0.1%, scandium is 0.2%, and europium is 0.1%. The rest is the same as Example 1.

[0086] Comparative Example 3

[0087] The difference between this comparative example and Example 1 is that yttrium is not contained. The rest is the same as Example 1.

[0088] Comparative Example 4

[0089] The difference between this comparative example and Example 1 is that scandium is not contained. The rest is the same as Example 1.

[0090] Comparative Example 5

[0091] The difference between this comparative example and Example 1 is that the degassing agent does not contain the graphite / nano-molybdenum nitride composite. The rest is the same as Example 1.

[0092] Comparative Example 6

[0093] The difference between this comparative example and Example 1 is that the graphite / nano-molybdenum nitride composite in the degassing agent is replaced by a mixture of graphite and nano-molybdenum nitride. The rest is the same as Example 1.

[0094] Test results

[0095] The heat-treatment-free aluminum alloys prepared in the embodiment and the comparative example were sampled and tested, and the performance test results shown in Table 1 were obtained.

[0096] Table 1 Performance test results

[0097]

[0098] According to Table 1, compared with the comparative example, the aluminum alloy yield strength of the embodiment reaches more than 146MPa, the tensile strength reaches more than 284MPa, and the elongation reaches more than 13.5. Among them, the best comprehensive performance is embodiment 4, with a yield strength of 152MPa, a tensile strength of 292MPa, and an elongation of 14.5, achieving a high level of strength and toughness of the die-cast aluminum alloy. It can be seen from the comparative example that a high silicon content will affect the elongation of the aluminum alloy, which may be due to the large eutectic silicon grains and the relatively coarse second phase formed. High yttrium, scandium and europium contents will affect the yield strength and tensile strength of the aluminum alloy, which may be due to the high burnout rate of the several at higher contents, and it is impossible to maintain a long dispersion strengthening and grain refinement effect. When yttrium and scandium are used alone, the effect is worse than when the two are used in combination, indicating that the combination of the two has a synergistic promotion effect and can significantly improve the performance of the aluminum alloy.

[0099] The microstructure of the aluminum alloy samples of Examples 1-4 was analyzed and the following results were obtained: Figure 1-8 The microstructure diagram shown. Figure 1-8 It can be seen that the grain size distribution of the aluminum alloys of Examples 1-4 is relatively uniform.

[0100] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A green aluminum heat-treatment-free die-casting aluminum alloy, characterized in that: The following components are included by mass fraction: silicon 4-5%, iron 0.2-0.5%, copper 0.1-0.5%, zinc 0.1-0.5%, manganese 0.3-0.6%, magnesium 0.1-0.3%, cadmium 0.1-0.5%, titanium 0.02-0.3%, strontium 0.002-0.1%, yttrium 0.001-0.02%, scandium 0.002-0.01%, europium 0.001-0.01%, and the balance is aluminum.

2. The method for preparing green aluminum heat-treatment-free die-casting aluminum alloy according to claim 1, characterized in that: The following steps are involved: Melting aluminum ingots, silicon, iron, copper, zinc, manganese, magnesium, cadmium, titanium, and green aluminum raw materials to prepare a first aluminum alloy melt; Adding strontium, yttrium, scandium and europium raw materials into the first aluminum alloy melt for smelting to obtain a second aluminum alloy melt; Adding a degassing agent to the second aluminum alloy melt for refining treatment, and slagging to obtain a third aluminum alloy melt; The third aluminum alloy melt is die-casted to obtain a lightweight heat-treatment-free die-cast aluminum alloy.

3. The method for preparing green aluminum heat-treatment-free die-casting aluminum alloy according to claim 2, characterized in that: The degassing agent comprises, by weight, 20-30 parts of magnesium chloride, 20-30 parts of potassium chloride, 10-20 parts of potassium fluoroaluminate, 20-30 parts of aluminum fluoride and 10-20 parts of graphite / nano-molybdenum nitride composite.

4. The method for preparing green aluminum heat-treatment-free die-casting aluminum alloy according to claim 3, characterized in that: The preparation method of the graphite / nano-molybdenum nitride composite is as follows: graphite is made into expanded graphite, a nano-molybdenum source is dissolved in a solvent to make a dispersion, the dispersion is injected between expanded graphite layers under vacuum pressure, the solvent is evaporated, heated and oxidized, and then nitrided in a nitrogen atmosphere to obtain the composite.

5. The method for preparing green aluminum heat-treatment-free die-casting aluminum alloy according to claim 2, characterized in that: During the refining process, chlorine gas is also introduced into the refining system at a flow rate of 20-30 L / min.

6. The method for preparing green aluminum heat-treatment-free die-casting aluminum alloy according to claim 2, characterized in that: The refining time is 10-20 minutes, and the mixture is allowed to stand for 5-10 minutes after refining.

7. The method for preparing green aluminum heat-treatment-free die-casting aluminum alloy according to claim 2, characterized in that: During die casting, the pressure is 60-70MPa, the temperature of the third aluminum alloy melt is 680-690℃, the mold temperature is 160-170℃, the speed is 3-4.5m / s, and the vacuum degree is 10-50mbar.